Validating compositional fluid flow simulations using 4D seismic interpretation and vice versa in the SECARB Early Test—A critical review. (March 2019) - Alfi, Masoud; Vasco, Donald W.; Hosseini, Seyyed A.; Meckel, Timothy A.; Hovorka, Susan D.
Highlights: Seismic data collected at Cranfield, MS CO2 -EOR project with three different interpretations is presented. Results obtained from these 3 different methods are mapped and compared among each other. A fluid flow numerical simulation study carried out and saturation profiles obtained from simulations were compared to seismic data interpretations. Selection of 3D seismic interpretation methods has large impact on the final results. Distribution of fluids (oil, gas, water) has an important role and can be very useful in integrated studies. Abstract: This paper discusses strengths and weaknesses of 4D seismic interpretation as a technique for monitoring carbon dioxide that was injected as part of a large scale test associated with commercial enhanced oil recovery (EOR) at Cranfield Field, Mississippi, USA. The goals of the monitoring effort are 1) to make measurements to verify that the CO2 is contained in the reservoir according to operational designs and model predictions, and 2) that if there are deviations, to provide data which can be used to update the earth models and determine if any mitigation is needed. The current work uses a compositional numerical simulation to model CO2 flow in the reservoir and compares the results with estimates of changes in seismic properties between a pre-injection and a survey after more than 2 million metric tons injected. The complicated physics of the problem in Cranfield field present challenges to seismic interpretations. Our results show partial agreement between the results of the numerical simulation and the seismic interpretations. Possible causes of discrepancies among the fluid flow model and multiple interpretations of the same seismic data sets performed with different work flows illuminates the types of uncertainties that should be considered to achieve the goals of monitoring.